A comprehensive test method for measuring actuation performance of McKibben artificial muscles. (8th March 2021) - Salahuddin, Bidita; Warren, Holly; Spinks, Geoffrey M
Abstract: The versatile nature of artificial muscles and their applications is derived from their ability to actuate in tensile, torsional and bending modes that can mimic the action of hydraulic rams, electric motors and biomimetic curling arms, respectively. Artificial muscles have exhibited great potential for fabricating robotic components and surgical tools due to their resemblance to biological muscles; along with their high actuation force per mass. For further investigation of these artificial muscles as tensile actuators with practical applications, it is imperative to standardise methods for characterising their performance. This article applies an integrated characterization method: simultaneously measuring the free stroke of a McKibben-type hydraulic artificial muscle; the stroke while operating against an externally applied force (isotonic); the blocked force of these muscles while keeping the muscle at constant length (isometric); and the force and displacement change when the muscle operates against a return spring (variable force, pressure). This linear mechanics approach has been verified and allows the prediction of these fundamental actuation characteristics while illustrating the effects of changing external load on the muscle performance. This study proposes an important approach to assist the design of McKibben muscles when used to carry variable loads such as in exoskeletons, prosthetics, and robotics applications.